2021
DOI: 10.11594/ijmaber.02.04.08
|View full text |Cite
|
Sign up to set email alerts
|

Social Contagion of Astrology in the Social Media amid COVID-19 Pandemic

Abstract: This cross-sectional study aimed to determine the associations of the extent of Social Contagion - Conscious Behavioral Response (CBR) towards Astrology on social media among Filipino Post-Millennial university students aged 18 to 23 years old with their demographics, Stress Level (SL), and Level of Susceptibility to Barnum effect (LSB) during the COVID-19 pandemic. A total of 406 respondents participated in the online survey and data were analyzed using descriptive and non-parametric inferential statistics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Unscientific personality assessments are beneficial to adolescents in the identity-cognition stage, increasing their ego identity. These results are in line with previous empirical studies in astrology, which showed that the contract of astrology information is related to the promotion of self-concept ( Lillqvist and Lindeman, 1998 ; Lopez et al, 2021 ). As mentioned above, ego identity can be understood as a maturity of self-concept ( Guo and Che, 2004 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Unscientific personality assessments are beneficial to adolescents in the identity-cognition stage, increasing their ego identity. These results are in line with previous empirical studies in astrology, which showed that the contract of astrology information is related to the promotion of self-concept ( Lillqvist and Lindeman, 1998 ; Lopez et al, 2021 ). As mentioned above, ego identity can be understood as a maturity of self-concept ( Guo and Che, 2004 ).…”
Section: Discussionsupporting
confidence: 92%
“…We measured Barnum effect susceptibility by adapting and translating the scale by Lopez et al (2021) . Based on this scale, the Barnum effect susceptibility level to the MBTI was examined in three dimensions: personal accuracy rating (“the personality traits about my MBTI are accurate”), interpretation favorability rating (“the MBTI affirms my inner self”), and interpretation exclusivity rating (“the MBTI interpretations suit my characteristics more than they do other people”).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be associated with the desire for meaning-making during times of stress as the need for meaning has been found to be a predictor of paranormal and religious beliefs (FioRito et al, 2021). And increased susceptibility to the Barnum effect is linked to increased consumption of astrology-related content (Lopez et al, 2021).…”
Section: Astrology and Stressmentioning
confidence: 99%